2022-RA-1506-ESGO Factors affecting survival rates of patients with uterine clear cell carcinoma. (20th October 2022) - Christodoulou, Theano; Pergialiotis, Vasilios; Prokopakis, Ioannis; Rodolakis, Ioannis; Haidopoulos, Dimitrios; Rodolakis, Alexandros; Thomakos, Nikolaos
Abstract : Introduction/Background: Uterine clear cell carcinoma represents a rare and aggressive gynecologic malignancy that is primarily treated with surgery. Chemotherapy and radiotherapy have been used as adjuvant therapy to postpone survival, however, even in this setting the actual mortality rates remain high. In the present study we evaluated factors that affect survival rates of patients, including patient and tumor characteristics as well as administered therapy. Methodology: The study was based in a retrospective cohort of patients treated in a tertiary university hospital in Greece. Cox regression analysis was used to evaluate the impact of age, body mass index, tumor size, stage of the disease at primary treatment, presence of upper abdominal metastases on survival rates of patients. Results: Overall, 53 patients were included in the present study with a median follow-up of 48 months. The median progression free survival was 36.47 months (29.78, 43.16) and the median overall survival was 47.35 months (39.89, 54.82). Advanced stage disease significantly decreased the rates of patient survival (29.80 vs 40.18 months for progression free survival and 43.30 vs 53.17 months for overall survival). Patients with metastases to the upper abdomen had the most decreased survival rates (11.6 months vs 39.59 months for progression free survival and 32.2 months vs 48.26 months for overall survival). The use of chemotherapy did not decrease recurrence rates HR 1.33, 95% CI 0.38, 4.71). Similar results were observed for external beam radiotherapy (HR 0.645, 95% CI 0.19, 2.21) and brachytherapy (HR 0.86, 95% CI 0.27, 2.76). Conclusion: Clear cell carcinoma is an extremely aggressive malignancy with survival rates of patients presenting at advanced stage being extremely short. Adjuvant therapy does not seem to benefit survival rates of patients with early stage disease.